HnRNPU/TrkB Defines a Chromatin Accessibility Checkpoint for Liver Injury and Nonalcoholic Steatohepatitis Pathogenesis. Issue 4 (24th January 2020) - Xiong, Jing; Liu, Tongyu; Mi, Lin; Kuang, Henry; Xiong, Xuelian; Chen, Zhimin; Li, Siming; Lin, Jiandie D.
Abstract : Background and Aims: Nonalcoholic steatohepatitis (NASH) is a progressive liver disease that is characterized by liver injury, inflammation, and fibrosis. NASH pathogenesis is linked to reprogramming of chromatin landscape in the liver that predisposes hepatocytes to stress‐induced tissue injury. However, the molecular nature of the putative checkpoint that maintains chromatin architecture and preserves hepatocyte health remains elusive. Approach and Results: Here we show that heterogeneous nuclear ribonucleoprotein U (hnRNPU), a nuclear matrix protein that governs chromatin architecture and gene transcription, is a critical factor that couples chromatin disruption to NASH pathogenesis. RNA‐seq and chromatin immunoprecipitation‐seq studies revealed an extensive overlap between hnRNPU occupancy and altered gene expression during NASH. Hepatocyte‐specific inactivation of hnRNPU disrupted liver chromatin accessibility, activated molecular signature of NASH, and sensitized mice to diet‐induced NASH pathogenesis. Mechanistically, hnRNPU deficiency stimulated the expression of a truncated isoform of TrkB (TRKB‐T1) that promotes inflammatory signaling in hepatocytes and stress‐induced cell death. Brain‐derived neurotrophic factor treatment reduced membrane TRKB‐T1 protein and protected mice from diet‐induced NASH. Conclusions: These findings illustrate a mechanism through which disruptions of chromatin architecture drive the emergence of disease‐specific signaling patterns that promote liver injury and exacerbate NASH pathogenesis.